Critical dialogical approach: A methodological direction for occupation-based social transformative work. (7th June 2019) - Farias, Lisette; Laliberte Rudman, Debbie; Pollard, Nick; Schiller, Sandra; Serrata Malfitano, Ana Paula; Thomas, Kerry; van Bruggen, Hanneke
Abstract: Background: Calls for embracing the potential and responsibility of occupational therapy to address socio-political conditions that perpetuate occupational injustices have materialized in the literature. However, to reach beyond traditional frameworks informing practices, this social agenda requires the incorporation of diverse epistemological and methodological approaches to support action commensurate with social transformative goals. Aim: Our intent is to present a methodological approach that can help extend the ways of thinking or frameworks used in occupational therapy and science to support the ongoing development of practices with and for individuals and collectives affected by marginalizing conditions. Method: We describe the epistemological and theoretical underpinnings of a methodological approach drawing on Freire and Bakhtin's work. Results: Integrating our shared experience taking part in an example study, we discuss the unique advantages of co-generating data using two methods aligned with this approach; dialogical interviews and critical reflexivity. Discussion: Key considerations when employing this approach are presented, based on its proposed epistemological and theoretical stance and our shared experiences engaging in it. Significance: A critical dialogical approach offers one way forward in expanding occupational therapy and science scholarship by promoting collaborative knowledge generation and examination of taken-for-granted understandings that shape individuals assumptions and actions.